2021
DOI: 10.1016/j.chest.2021.05.074
|View full text |Cite
|
Sign up to set email alerts
|

Executive Summary

Abstract: The current national coverage determinations (NCDs) for noninvasive ventilation for patients with thoracic restrictive disorders, COPD, and hypoventilation syndromes were formulated in 1998. New original research, updated formal practice guidelines, and current consensus expert opinion have accrued that are in conflict with the existing NCDs. Some inconsistencies in the NCDs have been noted, and the diagnostic and therapeutic technology has also advanced in the last quarter century. Thus, these and related NCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Reimbursement criteria are variable throughout the country. 61 The ONMAP Technical Expert Panel (Optimal Noninvasive Ventilation Medicare Access Promotion) recommendations for national coverage determination of NIV are less stringent in that no nocturnal hypoxemia is requisite, and greater clarity is provided for when more advanced home ventilation is needed over BPAP-S. 61 Patients newly initiated on NIV need to be evaluated on or after Day 61 of therapy to document that the patient reports benefit with use, and that there is use of device for at least 4 h per 24-h period. 66 Table 1 describes common modes of NIV, and Table 2 summarizes studies that observed use of home NIV in adult and pediatric CF patients, modes and settings utilized.…”
Section: Initiating Nivmentioning
confidence: 99%
See 1 more Smart Citation
“…Reimbursement criteria are variable throughout the country. 61 The ONMAP Technical Expert Panel (Optimal Noninvasive Ventilation Medicare Access Promotion) recommendations for national coverage determination of NIV are less stringent in that no nocturnal hypoxemia is requisite, and greater clarity is provided for when more advanced home ventilation is needed over BPAP-S. 61 Patients newly initiated on NIV need to be evaluated on or after Day 61 of therapy to document that the patient reports benefit with use, and that there is use of device for at least 4 h per 24-h period. 66 Table 1 describes common modes of NIV, and Table 2 summarizes studies that observed use of home NIV in adult and pediatric CF patients, modes and settings utilized.…”
Section: Initiating Nivmentioning
confidence: 99%
“…No CMS guidelines are currently present for guidance in obtaining more advanced devices. Reimbursement criteria are variable throughout the country 61 . The ONMAP Technical Expert Panel (Optimal Noninvasive Ventilation Medicare Access Promotion) recommendations for national coverage determination of NIV are less stringent in that no nocturnal hypoxemia is requisite, and greater clarity is provided for when more advanced home ventilation is needed over BPAP‐S 61 .…”
Section: Initiating Nivmentioning
confidence: 99%